Contrast sensitivity and glare in cataract using the Pelli-Robson chart. - Williamson, T. H. (1992)
There is a need for a convenient, clinically applicable test of glare disability which can be used in the preoperative evaluation of patients with cataract. In this study, contrast sensitivity (using the Pelli-Robson letter chart), near vision, and visual acuity were compared, with and without the introduction of a glare source in 70 patients with cataract, 15 with intraocular lenses, and 19 controls. A disposable pen torch was shone at the pupillary margin to induce glare. Contrast sensitivity demonstrated the most marked reduction during glare testing. Cortical cataracts were most affected followed by posterior subcapsular opacities. The glare disability was significantly less in pseudophakic patients and was absent from patients with non-cataractous phakic eyes. Glare testing with a disposable pen torch and a Pelli-Robson contrast sensitivity letter chart provides a rapid test of glare disability which can be easily incorporated into the clinical appraisal of patients with cataract.